2021
DOI: 10.1002/sctm.21-0086
|View full text |Cite
|
Sign up to set email alerts
|

Notch Signaling in the Dynamics of Perivascular Stem Cells and their Niches

Abstract: The Notch signaling pathway is a fundamental regulator of cell fate determination in homeostasis and regeneration. In this work, we aimed to determine how Notch signaling mediates the interactions between perivascular stem cells and their niches in human dental mesenchymal tissues, both in homeostatic and regenerative conditions.By single cell RNA sequencing analysis, we showed that perivascular cells across the dental pulp and periodontal human tissues all express NOTCH3, and that these cells are important fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 63 publications
(159 reference statements)
0
16
0
Order By: Relevance
“…Endothelial cells may interact with periodontal stem cells. Single cell RNA sequencing showed that periodontal stem cells express NOTCH3, and that the adjacent endothelial cells express all five NOTCH ligands, JAG1, JAG2, DLL1, DLL3, and DLL4, acting as niche‐derived modulator of periodontal stem cells (Pagella, de Vargas Roditi, Stadlinger, Moor, & Mitsiadis, 2021). Inhibition of Notch in vitro reduced the periodontal H type endothelium and down‐regulated coupled osteogenesis.…”
Section: Components Of Periodontal Stem Cell Nichementioning
confidence: 99%
“…Endothelial cells may interact with periodontal stem cells. Single cell RNA sequencing showed that periodontal stem cells express NOTCH3, and that the adjacent endothelial cells express all five NOTCH ligands, JAG1, JAG2, DLL1, DLL3, and DLL4, acting as niche‐derived modulator of periodontal stem cells (Pagella, de Vargas Roditi, Stadlinger, Moor, & Mitsiadis, 2021). Inhibition of Notch in vitro reduced the periodontal H type endothelium and down‐regulated coupled osteogenesis.…”
Section: Components Of Periodontal Stem Cell Nichementioning
confidence: 99%
“…During adulthood, Notch signalling plays an important role in regulating the behaviour of stem cells, by maintaining their stemness and influencing their fate in most tissues [17,18]. Notch signalling is active in various adult stem cell niches [19]. For example, interaction between Notch1 and Delta-like4 (Dll4) is necessary for establishing hematopoietic clusters in the aorta-gonad-mesonephros, which is the primordial niche for hematopoietic stem cells [20].…”
Section: Spheroidsmentioning
confidence: 99%
“…Notch signaling is an evolutionarily conserved, intercellular, and contact-dependent signaling pathway which regulates cell fate decisions and plays a significant role during development and organogenesis [5][6][7][8][9][10]. Many studies have demonstrated the critical role of Notch signaling in cell fate determination, cell proliferation, differentiation, and apoptosis in various cell types [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%